Radioactivity in Bananas : A Comparative Study of K40 Concentrations in Costa Rican and Ecuadorian Varieties Available in the Libyan Market (Comprehensive Journal of Science, 2025)
Bananas are a rich source of potassium, which naturally contains trace amounts of theradioactive isotope potassium-40. This study investigates the levels of radioactive potassium40 in bananas supplied to the Libyan market, with a focus on samples imported from CostaRica and Ecuador. Fifteen banana samples were collected, prepared, and analyzed usinggamma spectrometry with a high-purity germanium (HPGe) detector. The activityconcentrations of K⁴⁰ were found to range between 93.8±3.3 and 276.9±10.2 Bq/kg, withCosta Rican bananas exhibiting higher average concentrations (226.25±8.8 Bq/kg) comparedto Ecuadorian bananas (186.85±8.25 Bq/kg). The results indicate that while the levels of K⁴⁰in bananas are within safe limits, variations in concentrations may be influenced bygeographical and agricultural factors, such as soil composition and the use of potassium-richfertilizers. The study highlights the importance of monitoring radioactivity in food,particularly in regions with limited radiological data, and contributes to the globalunderstanding of radiological risks associated with food consumption. The findingsunderscore the need for further research into the factors affecting radionuclide uptake in crops
Keywords: Bananas, potassium-40, radioactivity, gamma spectrometry, Libyan market